MODELLING THE SUSTAINABILITY OF INTERNATIONAL ECONOMIC RELATIONS AND SUPPLY CHAIN OF THE WORLD STATES - Nurieva, R; Gibadullin, M.Z; Nasretdinov, I.T; Young Cheol, Ko; Karimova, G.R (International Journal of Supply Chain Management, 2020)
Abstract- Studying and monitoring the international cooperation zone allows us to take a fresh look at the integration processes in the system of world economic relations and answer the question about the nature and scale of international economic integration and globalization. This paper investigated the relationship between economy, supply chain management, international trade and international cooperation zone with mediation effect of international relations. The empirical basis of this study was the data of the state statistical service of the two largest economies in the Asia-Pacific region ? the Republic of Korea and Japan. As part of the study, the task was set to conduct a comparative analysis of the system of international economic relations of the Republic of Korea and Japan.